518. Model-informed Dose Selection of Dual Toll-like Receptor 7/8 Inhibitor Enpatoran (M5049) for the Treatment of COVID-19 Pneumonia. (4th December 2021) - Klopp-Schulze, Lena; Shaw, Jamie; Dong, Jennifer; Khandelwal, Akash; Adams, Elizabeth; Yu, Dongzi; Goteti, Kosalaram
Abstract: Background: Enpatoran, formerly known as M5049, is a potential first-in-class small molecule antagonist of toll-like receptors (TLR) 7 and 8, which may prevent viral-associated hyperinflammatory response and progression to 'cytokine storm' in coronavirus disease 2019 (COVID-19) patients. The objective of this study was to leverage existing population pharmacokinetic/pharmacodynamic (popPK/PD) models for enpatoran to inform dose selection for an accelerated Phase II study in COVID-19 patients with pneumonia. Methods: The popPK/PD models were based on plasma PK and PD biomarker (ex vivo-stimulated interleukin [IL]6 and interferon α [IFNα] secretion) data from the enpatoran first-in-human Phase I study in healthy participants (Port A, et al. Lupus Sci Med 2020;7(Suppl. 1): Abstract P135). A two-compartment model describing PK used a sigmoidal Emax model with proportional decrease from baseline characterizing the PD response across the investigated single and multiple daily dose range of 1–200 mg (N=72). Concentrations that inhibited 50% and 90% (IC50 /IC90 ) of cytokine secretion were estimated and stochastic simulations were performed to assess target coverage under different dosing regimens. Results: Simulations suggested that, to achieve maximal inhibition of IL-6 over time, enpatoran PK concentrations would be maintained above the IC90 throughout the dosing interval with doses of 100 mg and 50 mg twice daily in 90% and 30% of participants, respectively. In comparison, IFNα inhibition was predicted to be lower, with IC90 coverage in 60% and 8% of participants with twice daily doses of 100 mg and 50 mg enpatoran, respectively. Conclusion: Utilization of existing popPK/PD models allowed for the accelerated development of enpatoran in COVID-19 to address an unprecedented global pandemic. Rational model-informed dose selection was supported by data from a Phase I study in which there were no safety concerns. Disclosures: Lena Klopp-Schulze, PhD, Merck KGaA, Darmstadt, Germany (Employee) Jamie Shaw, BS, EMD Serono Research & Development Institute, Inc., Billerica, MA, USA (an affiliate of Merck KGaA, Darmstadt, Germany) (Employee) Jennifer Dong, PhD, EMD Serono Research & Development Institute, Inc., Billerica, MA, USA (an affiliate of Merck KGaA, Darmstadt, Germany) (Employee) Akash Khandelwal, PhD, Merck KGaA, Darmstadt, Germany (Employee, Shareholder) Elizabeth Adams, MD, BioNTech SE, Germany (Employee)EMD Serono Research & Development Institute, Inc., Billerica, MA, USA (an affiliate of Merck KGaA, Darmstadt, Germany)(employer at the time of study) (Employee) Dongzi Yu, MD, EMD Serono Research & Development Institute, Inc., Billerica, MA, USA (an affiliate of Merck KGaA, Darmstadt, Germany) (Employee) Kosalaram Goteti, PhD, EMD Serono Research & Development Institute, Inc., Billerica, MA, USA (an affiliate of Merck KGaA, Darmstadt, Germany) (Employee)Pfizer (Shareholder)